2020
DOI: 10.3390/microorganisms8020293
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Two Brominated Oxindole Alkaloids as Staphylococcal DNA Gyrase and Pyruvate Kinase Inhibitors via Inverse Virtual Screening

Abstract: In the present study, a small marine-derived natural products library was assessed for antibacterial potential. Among 36 isolated compounds, a number of bis-indole derivatives exhibited growth-inhibitory activity towards Gram-positive strains (Bacillus subtilis and multidrug-resistant Staphylococcus aureus). 5- and 6-trisindoline (5-Tris and 6-Tris) were the most active derivatives (minimum inhibitory concentration, MIC, 4–8 µM) that were subsequently selected for anti-biofilm activity evaluation. Only 5-Tris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 30 publications
(43 reference statements)
0
46
0
Order By: Relevance
“…In silico and in vitro results encouraged us to run an antibiotic synergistic study of these flavonoids with β-lactam antibiotic ampicillin ( Table 2). The result of this study indicated that hesperetin (6), apigenin (4), and chrysin (5) have an additive effect with the β-lactam antibiotic ampicillin (FICI = 1). However, the glycosylated derivatives, rutin (10), diosmin (11)…”
Section: In Vitro Inhibitory Activitymentioning
confidence: 88%
See 4 more Smart Citations
“…In silico and in vitro results encouraged us to run an antibiotic synergistic study of these flavonoids with β-lactam antibiotic ampicillin ( Table 2). The result of this study indicated that hesperetin (6), apigenin (4), and chrysin (5) have an additive effect with the β-lactam antibiotic ampicillin (FICI = 1). However, the glycosylated derivatives, rutin (10), diosmin (11)…”
Section: In Vitro Inhibitory Activitymentioning
confidence: 88%
“…On the other hand, the non-glycosylated flavonoids (compounds 1-6) showed interesting fitting inside the PBP2a active site with binding free energy values ranging from −7.0 to −8.0 kcal/mol, while the highly hydroxylated derivative myricetin (1) showed relatively weaker binding affinity (ΔG = −5.8 kcal/mol). Regardless, the convergent binding affinity and interaction modes of the derivatives 1-6 showed different MIC values against MRSA ranged from 15.62 µg/mL for chrysin (5) to 125 µg/mL for myricetin (1) ( Table 2). Being the smallest and the least hydroxylated (i.e., the least hydrophilic) molecule among its counterparts, particularly at ring B, chrysin (5) was able to easily access the PBP2a active site narrow groove during the 20 ns MDS ( Figure 4A,B).…”
Section: Docking Studies and Molecular Dynamic Simulation Refinementmentioning
confidence: 99%
See 3 more Smart Citations